Physicians' Attitudes Towards Artificial Intelligence: Results of the PEAK Project - Negash, Sarah; Gundlack, Jana; Buch, Charlotte; Apfelbacher, Timo; Christoph, Jan; Schildmann, Jan; Frese, Thomas; Mikolajczyk, Rafael (Digital Health and Informatics Innovations for Sustainable Health Care Systems. Proceedings of MIE 2024, 2024)
Artificial intelligence (AI) is rapidly reshaping the medical field. This study aimed to investigate the attitudes of physicians towards AI in medical care using focus groups. Most participants seemed to be open to the use of AI in medicine if transparency in AI systems is ensured, regulatory barriers are addressed and personal contact to the patient is maintained. This qualitative study allows insights into how German physicians perceive the use of AI in medical care. Gaining input from physicians is important when designing future applications of AI for the practical use in medical care.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Acceptance; Artificial Intelligence; Medical care; Perceptions; Physicians